Herpes Simplex Virus ICP0 and ICP34.5 Counteract Distinct Interferon-Induced Barriers to Virus Replication - Mossman, Karen L. (American Society for Microbiology, 2002)
Interferon inhibits virus replication through multiple mechanisms. Here we show that herpes simplex virus proteins ICP0 and ICP34.5 overcome interferon-induced barriers to viral transcription and translation, respectively. These cytokine-induced antiviral mechanisms are differentially expressed in established cell lines: U2OS cells do not mount the IFN-induced mechanism targeted by ICP0, and Vero cells may be defective for the mechanism targeted by ICP34.5.